Effect of Branch Pruning and Seed Seed Weight on Plant Growth and Years Potato (Solanum tuberosum L.) - Mimik Umi Zuhroh; Ida Sugeng Suyani (Universitas Muhammadiyah Sidoarjo, 2022)
The purpose of this study was to determine the effect of branch pruning and tuber weight on the growth and yield of potato. The research was carried out from April to July 2021 in the Mberas Hamlet, Tukul Village, Sumber District, Probolinggo Regency. This research was conducted using a factorial randomized block design method with two factors. The first factor was pruning secondary branches which consisted of 4 treatment levels. The second factor was the weight of the seed tubers which consisted of 3 treatment levels. Variable observations consisted of main plant height, number of main stems, number of leaves, number of cassava planted, weight of tubers planted, weight of wet stover, dry stover per plant, production per hectare. Data will be analyzed by means of the F test at the 5% level, if it shows significantly different results it will be followed by 5% BNT test for the single treatment and Ducan's multiple range test or DMRT at the 5% level for the interaction treatment. The conclusions of this study were P3 pruning treatment had a very significant effect on plant height parameters. Treatment of B3 seed tuber weight had a very significant effect on plant height parameters, number of stems main, number of leaves, number of tubers planted, weight of tubers planted, dry and wet stover. There was an interaction between the pruning treatment of six branches and the weight of the seed tubers of 40-49 g on the parameters of plant height aged 14.21 and 28 DAP